MEN BUYING BEHAVIOR ON PLUS SIZE JEANS PRODUCT IN BANDUNG - Krisna Widodo S, Lukas
Based on the data from Warta Pengkajian Perdagangan Volume 3 no. 12 Tahun 2016, the sales of jeans are increasing every year. In Indonesia the number of obesity is also continuing to keep increasing every year including in Bandung. This phenomenon gives the opportunity for Avant Grande, a big-size jeans company based in Bandung, to step in into the market and get the potential market to increase their big size jeans sales. Avant Grande has been facing sales issues, where their sales didn’t reach their target and did not achieve their expectation. The researcher wants to know the men buying behavior towards plus-size jeans in Bandung. The objective of this research is to find the purchase decision process of men on plus-size jeans and also understand men buying behavior on plus-size jeans purchasing. To collect the data, the researcher conducted a survey through an online questionnaire to 60 respondents and analyzed it using SEM PLS. From the research, the researcher found that the decision making process of men buying behavior on plus-size started from the firm’s attendance state. Then, it will be affected by the purchase environment factor. In the process of purchasing, an environment will influence how the customer chooses the product. After that men who use plus-size jeans will purchase a product then do a post-purchase activity. Based on the result of the study, men who use large-sized jeans prefer to purchase offline than online. This is because they can try directly to ensure a suitable size. The trend significantly influences their buying decision but their frequency to buy jeans is quite low, because the need to change the product every period is not really needed. Foreign brands are more preferred products to buy than local brands or taylor because they perceive it as more trusted. The result of this study can be a basis for making the right marketing strategy for SME that has a limited budget.